GT Factor ZmGT-3b Is Associated With Regulation of Photosynthesis and Defense Response to Fusarium graminearum Infection in Maize Seedling - Zhang, Qianqian; Zhong, Tao; E, Lizhu; Xu, Mingliang; Dai, Weixing; Sun, Shuchang; Ye, Jianrong (Frontiers in Plant Science, 2021)
It is of critical importance for plants to correctly and efficiently allocate their resources between growth and defense to optimize fitness. Transcription factors (TFs) play crucial roles in regulation of plant growth and defense response. Trihelix TFs display multifaceted functions in plant growth, development, and responses to various biotic and abiotic stresses. During our previous investigation of maize stalk rot disease resistance mechanism, we found a trihelix TF gene, ZmGT-3b, which is primed for response to Fusarium graminearum challenge by implementing a rapid and significant reduction of its expression to suppress seedling growth and enhance disease resistance. Consistently, ZmGT-3b knockdown led to diminished growth, but improved disease resistance and drought tolerance in maize seedlings. In ZmGT-3b knockdown seedlings, the chlorophyll content and net photosynthetic rate were significantly reduced, and the photosynthesis-related genes were specifically downregulated, especially ZmHY5, which encodes a conserved central regulator of seedling development and light responses. Moreover, ZmGT-3b knockdown synchronically induced defense-related transcriptional reprogramming and increased biosynthesis of lignin without immune activation, as the contents of major cell wall components, such as lignin, were increased and the genes associated with secondary metabolite biosynthesis and defense-related functions were significantly upregulated in the ZmGT-3b knockdown seedlings. These suggest that ZmGT-3b involves in coordination of the metabolism during growth-to-defense transitions by optimizing the temporal and spatial expression of photosynthesis- and defense-related genes.